Involvement of fibroblast growth factor 2 (FGF2) and its receptors in the regulation of mouse sperm physiology. Issue 2 (August 2018) - Saucedo, Lucía; Sobarzo, Cristian; Brukman, Nicolás G; Guidobaldi, Héctor A; Lustig, Livia; Giojalas, Laura C; Buffone, Mariano G; Vazquez-Levin, Mónica H; Marín-Briggiler, Clara
Abstract : Fibroblast growth factor 2 (FGF2) and its receptors (FGFRs) have been described in several tissues, where they regulate cellular proliferation, differentiation, motility and apoptosis. Although FGF2/FGFRs expression in the male reproductive tract has been reported, there is scarce evidence on their presence in the female reproductive tract and their involvement in the modulation of sperm function. Therefore, the objective of this study was to determine the expression of FGF2 in the female reproductive tract and to assess the role of the FGF2/FGFRs system in the regulation of sperm physiology using the murine model. FGF2 was detected in uterus and oviduct protein extracts, and it was immunolocalized in epithelial cells of the uterus, isthmus and ampulla, as well as in the cumulus oophorus -oocyte complex. The receptors FGFR1, FGFR2, FGFR3 and FGFR4 were immunodetected in the flagellum and acrosomal region of sperm recovered from the cauda epididymis. Analysis of testis sections showed the expression of FGFRs in germ cells at different stages of the spermatogenesis, suggesting the testicular origin of the sperm FGFRs. Sperm incubation with recombinant FGF2 (rFGF2) led to increased sperm motility and velocity and to enhanced intracellular Ca 2+ levels and acrosomal loss compared to the control. In conclusion, this study shows that FGF2 is expressed in tissues of the female reproductive tract. Also, the fact that functional FGFRs are present in mouse sperm and that rFGF2 affects sperm motility and acrosomal exocytosis, suggests the involvement of this system in the in vivo regulation of sperm function.